Determination of Frame for Tsunami Capsule Passengers Based on the Results of Stress and Strain using Octahedral Discretization - Mochamad Edoward Ramadhan; Gaguk Djatisoekamto (University of Muhammadiyah Jakarta, 2020)
The prototype research for the safety capsule began with the tsunami that struck Indonesia as an archipelago. Also, the United States, Japan, and China have made successful tsunami capsules in patent RIGHTS with the code US4297757 (America) spherical and in China, there are about 5 shapes that have been made CN102267549B (mushroom forms); CN203698627U (cup shape); CN204750532U (bunker form); CN204916125U (cylindrical capsule form); CN208198781U (ovoid shape). After examining existing patents and prototypes, the researchers made a prototype in the shape of a ball with a diameter of 2 meters. The material uses Stainless steel outer diameter of 25.4mm and an inner diameter of 23.9mm. The simulation uses octahedral discretion by mesh adjusting to the structure. The load uses pressure in the outer surface area, a person load of 4 with a weight of 60kg each, and for fixed constraints on the inside of spherical geometry. The purpose of the simulation is to predict the location of critical areas that experience the greatest stress and strain. The concept is applied based on the number of amplifiers given in the form of a square as a reference, the concept of 1 amplifier is given a vertical direction, the concept of 2 vertical and horizontal directions, the concept of 3 diagonal crosswise, the concept of 4 diagonal crosses and 1 amplifier of the vertical direction, the concept of 5 diagonal crosses and the direction horizontal vertical, the concept of 6 square in the middle with vertical and horizontal amplifiers, the concept of 7 square in the middle with the diagonal crossing amplifier, the concept of 8 triangles in the middle with the bottom diagonal in the middle and one horizontal direction, the concept of 9 triangles in the middle with crossed diagonals and added a directional line horizontally, the concept of 10 hexagons with the edges is given an amplifier up to the frame. The results of the simulation selection, concept 3, and Concept 6 have a strain of 0.00725mm, while Concept 6 has principal stress smaller than Concept 3 which is 3.05x106N / m with an estimated local error of 2.13 x 10-6 Joules. So that Concept 6 is set to be used as an amplifier of prototype tsunami safety capsules.